2015
DOI: 10.1007/s11004-015-9598-6
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical look at Ensemble-Based Optimization in Reservoir Management

Abstract: Ensemble-based optimization has recently received great attention as a potentially powerful technique for life-cycle production optimization, which is a crucial element of reservoir management. Recent publications have increased both the number of applications and the theoretical understanding of the algorithm. However, there is still ample room for further development since most of the theory is based on strong assumptions. Here, the mathematics (or statistics) of Ensemble Optimization is studied, and it is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…In EnOpt, u is considered to be a random vector with a Gaussian distribution centered at u ℓ and covariance matrix boldCboldU, that is, at iteration ℓ , bolduscriptN(boldu,boldCboldU). This notation indicates that it is possible to generate a new covariance matrix, for example, by covariance matrix adaptation . For our purposes, however, it suffices to consider the covariance matrix as fixed so we assume throughout that bolduscriptN(boldu,boldCboldU) at iteration ℓ .…”
Section: Ensemble Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In EnOpt, u is considered to be a random vector with a Gaussian distribution centered at u ℓ and covariance matrix boldCboldU, that is, at iteration ℓ , bolduscriptN(boldu,boldCboldU). This notation indicates that it is possible to generate a new covariance matrix, for example, by covariance matrix adaptation . For our purposes, however, it suffices to consider the covariance matrix as fixed so we assume throughout that bolduscriptN(boldu,boldCboldU) at iteration ℓ .…”
Section: Ensemble Optimizationmentioning
confidence: 99%
“…Stordal et al . recently provided a theoretical analysis of the single and multiple reservoir formulations of standard EnOpt in which they demonstrate that both can be interpreted as special versions of a machine learning algorithm called ‘Gaussian mutation optimization’ . Stordal et al .…”
Section: Ensemble Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereafter this will be referred to as the "original formulation". In Stordal et al (2014) it is shown how this implementation converges to the exact gradient in a natural evolutionary framework. Fonseca et al (2014) investigated the applicability of EnOpt for multi-objective optimization based on a single model realization and showed results which suggest that EnOpt is a viable alternative when the adjoint is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Stochastic methods vary uncertain input parameters from a probability distribution function to create an ensemble of model predictions or optimization results [45,46]. The predictions that most closely align with the measurements are selected to find an optimal solution to the history matching problem.…”
Section: History Matching For Waterflood and Enhanced Oil Recoverymentioning
confidence: 99%